(untitled) (Scientific journal of the Fergana State University, 2024)
This article, based on an assessment of the socio-economic potential of the Fergana region, examines the possibilities of improving the tourism and recreational system at the district level. A grouping of administrative districts of the Fergana region according to tourism and recreational potential was also carried out.